2015
DOI: 10.1128/aem.02971-14
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Porcine Gastric Mucin Binding Assay for High-Pressure-Inactivation Studies Using Murine Norovirus and Tulane Virus

Abstract: We compared the results of high-hydrostatic-pressure (HHP) inactivation of murine norovirus type 1 (MNV-1) and Tulane virus (TV) obtained by a porcine gastric mucin binding assay followed by quantitative reverse transcription-PCR (referred to here as the PGM-MB/PCR assay) and a plaque assay and evaluated HHP inactivation of a human norovirus (HuNoV) genogroup I genotype 1 (GI.1) strain and a HuNoV GII.4 strain by using the PGM-MB/PCR assay. Viruses were treated at different pressure levels for 2 min at 4 or 21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 35 publications
1
26
0
Order By: Relevance
“…The 2 pressure inactivation curves for MNV‐1 and TV obtained using the plaque and PGM‐MB/PCR assays were almost identical at less than approximately 2 log 10 reduction levels. We concluded that the PGM‐MB binding assay would be very likely able to correctly quantify HHP inactivation of HuNoV at less than 2 log 10 ‐reduction levels and also likely to correctly or conservatively quantify HHP inactivation of HuNoV at 2 to 3.5 log 10 ‐reduction levels (Li and Chen ). Taking together, the PGM‐MB binding method could potentially reflect the infectivity of HuNoV in oysters after HHP and thus, it was adopted in this study.…”
Section: Resultsmentioning
confidence: 99%
“…The 2 pressure inactivation curves for MNV‐1 and TV obtained using the plaque and PGM‐MB/PCR assays were almost identical at less than approximately 2 log 10 reduction levels. We concluded that the PGM‐MB binding assay would be very likely able to correctly quantify HHP inactivation of HuNoV at less than 2 log 10 ‐reduction levels and also likely to correctly or conservatively quantify HHP inactivation of HuNoV at 2 to 3.5 log 10 ‐reduction levels (Li and Chen ). Taking together, the PGM‐MB binding method could potentially reflect the infectivity of HuNoV in oysters after HHP and thus, it was adopted in this study.…”
Section: Resultsmentioning
confidence: 99%
“…When PGM was used to evaluate the inactivation of GI.1 Norwalk virus by high-pressure processing, reductions corresponded to those observed in a human feeding study with the same virus (11, 12). On the other hand, Li and Chen (9) found that their PGM binding assay correlated with infectivity assay results for Tulane virus and murine norovirus treated with high pressure at a ≤2-log 10 reduction, but the infectious virus titer was overestimated at higher degrees of inactivation. Another recent report found that PGM binding was more conservative than other in vitro infectivity assays for Tulane virus (29).…”
Section: Discussionmentioning
confidence: 99%
“…One method that is widely used is viral receptor binding, most commonly done with histo-blood group antigens (HBGAs). HBGA (or porcine gastric mucin [PGM], which contains some HBGAs) binding has performed well in comparison with the plaque assay when murine norovirus and Tulane virus surrogates were subjected to a variety of physical and chemical stresses (810). In the most compelling work yet, GI.1 Norwalk virus inactivation estimated by a combined PGM binding RT-qPCR method compared favorably to results from a parallel human challenge study evaluating the efficacy of high-pressure processing on norovirus in oysters (11, 12).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, different inactivation mechanisms (UV treatment, chlorination, etc.) should be explored because the effectiveness of photoactivable dye-based methods can provide different infectivity profiles [28].…”
Section: Discussionmentioning
confidence: 99%